Effects of Soil Properties on Phytoextraction of Cd and the Associated Soil Bacterial Communities across Four Soil Types. Issue 3 (3rd April 2022) - Hou, Fen; Du, Junjie
ABSTRACT: Soils are one of the repositories for heavy metal. Phytoextraction with hyperaccumulator Tagetes patula ( T.patula ) has great promise for the cadmium (Cd) removal from contaminated soils. However, there is lack of information about the effects of soil types with different properties on the phytoextraction efficiency and the associated bacterial communities. A pot experiment was performed for 90 d, with four types of soil (black soil, paddy soil, oasis soil, and fluvo-aquic soil) artificially contaminated with Cd at 10 mg kg −1 soil. T.patula showed the greatest Cd uptake efficiency in black soil, followed by paddy soil, oasis soil and fluvo-aquic soil, respectively. Across the four soils, soil pH had the strongest impact on Cd bioaccumulation in T.patula . The Cd uptake amount in T.patula shoot positively correlated with soil CEC, organic matter, total N, total P and total K, and negatively correlated with soil pH and soil particle size. Black soil showed the highest diversity of bacterial community, followed by the paddy, oasis, and fluvo-aquic soils. The structure of communities was altered after phytoremediation albeit to a small degree. Proteobacteria, Acidobacteria, Chloroflexi, Firmicutes, Actinobacteria, Planctomycetes, Gemmatimonadetes, and Bacteroidetes dominated the four soils with different abundances. Soil particle size and CEC had significant negative and positive effects on the richness of the bacterial communities, respectively. These results are important to develop the application of phytoremediation by T. patula in a wide range of Cd-contaminated soils.